The serrated pathway in colorectal carcinogenesis - Yamine, Letícia (2014)
Serrated adenocarcinoma is a recently described subset of colorectal cancer (CRC), which account for about 10% of all CRCs and follows an alternative pathway in which serrated polyps replace the traditional adenoma as the precursor lesion to CRC. Serrated polyps form a heterogeneous group of colorectal lesions that includes hyperplastic polyps (HPs), sessile serrated adenoma (SSA), traditional serrated adenoma (TSA) and mixed polyps. HPs are the most common serrated polyp followed by SSA and TSA. This distinct histogenesis is believed to have a major influence in prevention strategies, patient prognosis and therapeutic impact. Genetically, serrated polyps exhibited also a distinct pattern, with KRAS and BRAF having an important contribution to its development. Two other molecular changes that have been implicated in the serrated pathway include microsatellite instability and the CpG island methylator phenotype. In the present review we will address the current knowledge of serrated polyps, clinical pathological features and will update the most recent findings of its molecular pathways. The understanding of their biology and malignancy potential is imperative to implement a surveillance approach in order to prevent colorectal cancer development.